(untitled) (Journal of the College of Basic Education, 2019)
The present research aims to identify the Social Consciousness of the children of kindergarten. The sample included 200 children from kindergartens in the city of Baghdad. In order to achieve the research objectives, the researcher constructed the Social Consciousness after studying the theories and previous studies related to her research. Social awareness in its final form (28) paragraph and gave each position three alternatives, representing each of the paragraphs of the measure of Social Consciousness of the child has achieved the researcher of the standard characteristics of the instrument. The researcher reached the following results: ـ objective is that the children of kindergarten enjoy Social Consciousness. ـ There are differences between the average estimates of males and females in the scales of social awareness scale in favor of females. ـ The existence of differences in the social Consciousness scale according to the academic achievement of the parents of the research sample and the presence of differences according to the academic achievement of the children of the research sample